Impact of Vocational Training on Value Addition in Knowledge and Adoption of Rural Women - Ankita Pandey , Nishith Gupta , Akanchha Pandey and Sarita Singh, (Indian Journal of Extension Education, 2017)
The present study was conducted by Krishi Vigyan Kendra, Dewas for three years i.e. 2011-12, 2012-13 and 2013-14 withthe objective to find out the effectiveness of vocational training programme on knowledge and adoption of value additionof food grains, fruits and vegetables among rural women. The data revealed that just after completion of training, majority(63.33%) of trainees were having high level of knowledge regarding value addition followed by 36.66 per centrespondents having medium level of knowledge. After seven days of training, most (56.66%) of the trainees had mediumlevel of knowledge followed by high level (43.33%), while, none of the trainees had low level of knowledge. The resultsclearly indicated that vocational training on value addition was effective in enhancing the knowledge and adoption oftrainee. Therefore, it could be implied that more and more such training programmes on value addition may be organizedwhich would benefit rural women in particular and farming community in general.